Near-field radiative heat transfer between uniaxial hyperbolic media: Role of volume and surface phonon polaritons. (January 2021) - Wu, Xiaohu; Fu, Ceji
Highlights: Identified spectral conditions for HSPPs supported by hBN. Identified regions in k-plane for HVPPs and HSPPs supported by hBN. Identified thickness effect on near-field radiative flux between hBN slabs. Identified thickness effect on dispersion relation of HVPPs and HSPPs of hBN slab. Abstract: It has been found that near-field radiative heat transfer (NFRHT) between hyperbolic media, such as hexagonal boron nitride (hBN), can be significantly enhanced due to excitation of hyperbolic volume phonon polaritons (HVPPs) and hyperbolic surface phonon polaritons (HSPPs). However, the role of HVPPs and HSPPs in type I and type II hyperbolic bands has rarely been discussed in depth. In this paper, we investigate the NFRHT between two hBN slabs considering the role of HVPPs and HSPPs. The theoretical analysis and numerical results show that when the optical axis is perpendicular to the material surface, the enhanced NFRHT is attributed to the excitation of HVPPs in both type I and type II hyperbolic bands, while HSPPs cannot be excited in this case. When the optical axis is parallel to the material surface, only HVPPs can be excited in type I hyperbolic band, while both HVPPs and HSPPs can be excited in type II hyperbolic band. In addition, the effect of the slab thickness on the dispersion relations of HVPPs and HSPPs, and on the enhancement of NFRHT is also studied. We believe the results in this paper could help to elucidate the mechanisms and manipulation of enhanced NFRHT between uniaxial hyperbolic materials.